The Human Intellect: Liberation or Limitation?: Some Notes on ʿAql in Classical Islamic Mysticism - Ebstein, Michael (Journal of Sufi studies, 2019)
The article discusses various attitudes towards the human intellect (ʿaql) in classical Islamic mysticism, as reflected in key mystical writings composed from the third/ninth century to the rise of Ibn al-ʿArabī in the sixth/twelfth. It begins by presenting the basic challenge that the concept of ʿaql posed for the mystics of Islam and then proceeds to analyze diverse approaches to the intellect in works that were written in both the east (mashriq) and the west (al-Andalus). Special attention is given to the impact of Neoplatonism on mystical attitudes towards the intellect. The conclusion to the article offers general observations on the problem of ʿaql in classical Islamic mysticism, and attempts to explain the tendency of certain sixth/twelfth-century mystics who were exposed to Neoplatonic thought to reduce the role of the intellect in the mystical quest for God.